POLITICAL AND ECONOMIC COMPETITIVENESS OF EUROPE AND RUSSIA: OPPORTUNITIES FOR SYNERGY - V. I. Yakunin (Сравнительная политика, 2015)
Increasing global competition creates threats for Russia and Europe to remain independent centres of power. However, they could strengthen their standing through deepen cooperation with each other. Throughout the last two decades serious and repeating but unsuccessful attempts were made for such cooperation. The article examines both prerequisites and obstacles to the preferential partnership between Russia and Europe.